Insurance Status Impacts Hospital Discharge for Penetrating Trauma Survivors. Issue 8 (August 2022) - Olafson, Samantha N.; Cohen, Ryan B.; Parsikia, Afshin; Moran, Benjamin; Kaplan, Mark J.; Leung, Pak
Background: Despite equalized acute care in trauma, disparities exist in the long-term outcomes of trauma survivors. Prior studies have revealed insurance status plays a role in the discharge destination of blunt trauma survivors. This is yet to be described in patients with penetrating traumatic injury. Methods: A retrospective chart review from 2009 to 2019 from an urban Level 1 trauma center identified adult patients who survived penetrating trauma to discharge. Patients were categorized by insurance status. Patient demographics, discharge destination, and hospital length of stay (LOS) were analyzed using the t-test and ANOVA. Results: 1806 patients were identified with 1410 survivors to hospital discharge. Among the survivors, 26.8% were uninsured, 13.1% were privately insured, and 60.0% had Medicare/Medicaid. The uninsured patients were significantly less likely to be discharged to a rehabilitation facility or skilled nursing facility (OR = .49, 95% CI .35-.71) compared to the insured patients. Uninsured survivors had shorter LOS compared to the other groups (5.8 vs. 7.3, P < .01.) Severity of injury did not significantly influence the discharge destination or LOS between the groups. Conclusion: Despite recent health care reform, many trauma patients remain uninsured. Our study shows that uninsured penetrating trauma survivors are less likely to be discharged to rehabilitation and skilled nursing facilities. This may contribute to uninsured trauma survivors not receiving appropriate post-traumatic care and could lead to the accrual of undue disability, long-term complications, and increased societal burdens.